Do intellectual property rights influence cross-border mergers and acquisitions? - Mercedes Campi; Marco Due\~nas; Matteo Barigozzi; Giorgio Fagiolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
This paper analyses whether the strengthening of intellectual property rights (IPRs) systems affects decisions of cross-border mergers and acquisitions (M&As), and whether their influence is different for developed and developing countries and across industrial sectors. We estimate an extended gravity model to study bilateral flows of M&As using data for the post-TRIPS period (1995-2010) and two different indexes that measure the strength of IPRs systems at the country level. We find that IPRs influence decisions of cross-border M&As and facilitate the creation of investment linkages. However, we detect a heterogeneous impact of IPRs on M&As depending on specificities of countries and sectors.
Keywords: O34; G34; O13; O14; 330; Intellectual Property Rights; Mergers and Acquisitions; Technological Intensity; Gravity Model